Northern and Arctic air connectivity in Canada - Mike Tretheway; Robert Andriulaitis; Jody Kositsky; Geneva Tretheway (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
This paper examines explicit northern and Arctic connectivity policies in Canada, recognising the vital importance of air services in economic and social life. It comments on existing legislation, regulations, policies and programmes of the federal government as well as of Canada's three northern territories. It also looks at recommendations from past transport policy reviews.
Keywords: 330; Verkehrsinfrastruktur; Luftverkehrspolitik; Luftverkehr; Kanada (Nord); Arktis